2007
DOI: 10.1073/pnas.0701061104
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis primary microRNA processing proteins HYL1 and DCL1 define a nuclear body distinct from the Cajal body

Abstract: Small regulatory microRNAs (miRNAs) are encoded in long precursors and are released from them during processing by cleavage within partially duplexed stem-loop structures. In the present work we investigated the role of the Arabidopsis nuclear RNA-binding protein HYL1 and the nuclear RNase III enzyme DCL1 in processing of primary miRNA (pri-miR171a). The miR171a gene is complex, with multiple transcription start sites, as well as alternative splicing of exons and alternative polyadenylation sites. Both HYL1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
209
2
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(225 citation statements)
references
References 29 publications
11
209
2
3
Order By: Relevance
“…Recent studies have localized the miRNA biogenesis machinery proteins DCL1, DRB1 and SE to the nucleus specialized D-bodies. 10,11 In addition, HEN1 and AGO1 also show some localization to the nucleus and to D-bodies. 11 In plants, the Slicer activity of AGO1 specifically co-elutes with a small protein complex, 19 to suggest that miRNA-loaded RISC may consist of little more than AGO1 and its loaded sRNA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have localized the miRNA biogenesis machinery proteins DCL1, DRB1 and SE to the nucleus specialized D-bodies. 10,11 In addition, HEN1 and AGO1 also show some localization to the nucleus and to D-bodies. 11 In plants, the Slicer activity of AGO1 specifically co-elutes with a small protein complex, 19 to suggest that miRNA-loaded RISC may consist of little more than AGO1 and its loaded sRNA.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 In addition, HEN1 and AGO1 also show some localization to the nucleus and to D-bodies. 11 In plants, the Slicer activity of AGO1 specifically co-elutes with a small protein complex, 19 to suggest that miRNA-loaded RISC may consist of little more than AGO1 and its loaded sRNA. Our molecular analyses strongly suggest that miRNA precursor transcripts, namely the primiRNA are the target of amiRNA-directed anti-miRNA silencing technology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many, if not all, of the pleitropic phenotypes of these mutants can be explained by miRNA biogenesis defects. Recently, several groups discovered that these three proteins can interact with each other in vitro and in vivo, and at least part of them colocalize in the same subnuclear bodies that also contain pri-miRNAs (15)(16)(17). The exciting work of Dong et al (13) nicely explains why HYL1 and SE are required for miRNA biogenesis.…”
mentioning
confidence: 89%
“…43 Pri-miRNA polyadenylation site selection depends on the functional 5′ splice site Studies on plant pri-miRNA structures revealed that multiple polyadenylation sites might co-exist. 40,49,50 In the case of Arabidopsis pri-miR163, 2 polyA sites were identified: the proximal site that is located within the intron, and the distal site which is located at the end of the gene. 42,43 In the wild type A. thaliana cells, 60% of pri-miR163 is terminated at the distal site.…”
mentioning
confidence: 99%